A new miniature Priocharax from the río Putumayo drainage, Amazonas State, Colombia (Teleostei: Characiformes: Characidae) with an unusual skin flap between pelvic fins - Mattox, George Mendes Taliaferro; Acosta-Santos, Astrid; Gregory, Juan D. Bogotá-; Agudelo, Edwin; Lima, Flávio C. T. (Zootaxa, 2025)
The miniature fish genus Priocharax currently comprises nine valid species: P. ariel, P. britzi, P. conwayi, P. marupiara, P. nanus, P. phasma, P. pygmaeus, P. toledopizae and P. varii. Except for P. ariel and P. pygmaeus, all remaining species are endemic to Brazil. Priocharax is characterized by several paedomorphic features such as reductions in the laterosensory system, number of fin rays, and ossification of parts of the skull. The most striking reductive character of Priocharax is the larval rayless pectoral fin in which most of its endoskeletal part is absent. A new species of Priocharax is described herein from the río Putumayo drainage, Departamento Amazonas, Colombia. The new species is distinguished from all other congeners by a unique round flap of skin between contralateral pelvic fins.